Barossa Night: cohesion in the British Army officer corps - Bury, Patrick (The British journal of sociology, 2017)
Contrasting the classical explanation of military group cohesion as sustained by interpersonal bonds, recent scholars have highlighted the importance of ritualized communication, training and drills in explaining effective military performance in professional armies. While this has offered a welcome addition to the cohesion literature and a novel micro‐sociological method of examining cohesion, its primary evidential base has been combat groups. Indeed, despite their prominent role in directing operations over the past decade, the British Army's officer corps has received relatively little attention from sociologists during this period. No attempt has been made to explain cohesion in the officer corps. Using a similar method to recent cohesion scholars, this paper seeks to address this imbalance by undertaking a micro‐sociology of one ritual in particular: ‘Barossa Night’ in the Royal Irish Regiment. Firstly, it draws on the work of Durkheim to examine how cohesion amongst the officer corps is created and sustained through a dense array of practises during formal social rituals. It provides evidence that the use of rituals highlights that social solidarity is central to understanding officer cohesion. Secondly, following Hockey's work on how private soldiers negotiate order, the paper shows how this solidarity in the officer corps is based on a degree of negotiated order and the need to release organizational tensions inherent in a strictly hierarchical rank structure. It highlights how the awarding of gallantry medals can threaten this negotiated order and fuel deviancy. In examining this behaviour, the paper shows that even amongst an officer class traditionally viewed as the elite upholders of organizational discipline, the negotiation of rank and hierarchy can be fluid. How deviant behaviour is later accepted and normalized by senior officers indicates that negotiated order is as important to understanding cohesion in the British Army's officer corps as it is amongst private soldiers.